"We Are Trying to Communicate the Best We Can": Understanding Districts' Communication on Twitter During the COVID-19 Pandemic. (February 2022) - Michela, Esther; Rosenberg, Joshua M.; Kimmons, Royce; Sultana, Omiya; Burchfield, Macy A.; Thomas, Tayla
While educators' uses of social media for purposes such as professional learning and networking are now well-established, our understanding of how educational institutions use social media—including to engage key stakeholders during periods of crisis—is limited. In this study, we used a public data mining research approach to examine how K–12 school districts in the United States used Twitter as a communication tool during a critical period of the COVID-19 pandemic, March-April, 2020. Through a three-step grounded theory approach of 1, 357 district tweets from 492 school districts, we found that districts worked to build community and share time-sensitive announcements in alignment with social media crisis communication recommendations. Announcements were more common during the early stages of the pandemic (and were engaged more collaboratively), with community-building posts more common later on. This study demonstrates how researchers can use publicly available (social media) data to understand districts' communication priorities and strategies during and beyond periods of crisis.